Circulating Galectin-3 and Atrial Fibrillation Recurrence after Catheter Ablation: A Meta-Analysis - Guangping Zhang; Yongquan Wu (Cardiovascular Therapeutics)
Background. Galectin-3 (Gal-3) is involved in fibrosis and heart failure. However, epidemiological studies evaluating the association between Gal-3 and atrial fibrillation (AF) recurrence after catheter ablation showed inconsistent results. We conducted a meta-analysis to comprehensively evaluate the relationship between baseline circulating Gal-3 levels and AF recurrence in patients undergoing catheter ablation. Methods. Relevant studies were identified by systematically searching the PubMed and Embase databases. A random-effect model was used to synthesize the results. Sensitivity analyses, performed by omitting one study at a time, were used to evaluate the robustness of the results. Results. Seven prospective cohort studies including 645 AF patients were included. Within a follow-up duration of up to 18 months, 244 patients developed AF recurrence. Pooled results showed that baseline circulating Gal-3 levels were significantly higher in patients with AF recurrence compared to those without (standardized mean difference: 0.74; 95% confidence interval (CI): 0.21 - 1.27; p = 0.007; I2 = 89%). Moreover, higher baseline Gal-3 levels were independently associated with a significantly higher risk of AF recurrence after catheter ablation (risk ratio: 1.17 per unit of Gal-3; 95% CI: 1.01 - 1.35; p = 0.03; I2 = 40%), which was independent of age, gender, and left atrial dimension. Sensitivity analyses did not significantly affect the results. However, there was a significant publication bias for predicting efficacy of associating preprocedural Gal-3 levels with AF recurrence. Conclusions. Higher preprocedural Gal-3 levels may be associated with increased risk of AF recurrence in patients undergoing catheter ablation.